2008
DOI: 10.1038/sj.mp.4002149
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety is associated with reduced central serotonin transporter availability in unmedicated patients with unipolar major depression: a [11C]DASB PET study

Abstract: Serotonergic dysfunction may contribute to negative mood states in affective disorders. Some in vivo imaging studies showed reduced availability of serotonin transporters (5-HTT) in the brainstem and thalamus of patients with major depression. We tested the hypothesis that 5-HTT availability is reduced in unmedicated unipolar patients with major depression compared to healthy control subjects matched for gender, age, genotype and smoking status. Availability of 5-HTT was measured in vivo with positron emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
3
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(95 citation statements)
references
References 42 publications
(61 reference statements)
9
82
3
1
Order By: Relevance
“…Excluding subjects with mental disorders from this study limits the generalizability of the results to the healthy population. Exclusion of subjects with mental disorders is a valid approach, as some reports suggest decreased in vivo 5-HTT binding in major depression although this remains controversial with possible state-dependent phenomena involved (Bhagwagar et al 2007 ;Cannon et al 2007 ;Meyer, 2007 ;Reimold et al 2008 ;Selvaraj et al 2011). It is known that high HA predisposes to psychiatric disorders, especially in the mood and anxiety spectrum (see Miettunen & Raevuori, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Excluding subjects with mental disorders from this study limits the generalizability of the results to the healthy population. Exclusion of subjects with mental disorders is a valid approach, as some reports suggest decreased in vivo 5-HTT binding in major depression although this remains controversial with possible state-dependent phenomena involved (Bhagwagar et al 2007 ;Cannon et al 2007 ;Meyer, 2007 ;Reimold et al 2008 ;Selvaraj et al 2011). It is known that high HA predisposes to psychiatric disorders, especially in the mood and anxiety spectrum (see Miettunen & Raevuori, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A total of six published studies have used PET or single photon emission computed tomography to examine the correlation of serotonergic neurotransmission with HA (Rabiner et al 2002 ;Moresco et al 2002 ;Borg et al 2003 ;Van Heeringen et al 2003 ;Reimold et al 2008 ;Karlsson et al 2009 (Rabiner et al 2002 ;Borg et al 2003 ;Karlsson et al 2009) and one examining serotonin transporter 5-HTT with (Reimold et al 2008) in healthy subjects found no correlation between serotonin function and HA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decline with age is described for the 5-HT 1A receptors in both genders (Moller et al, 2007;Tauscher et al, 2001), in women only (Costes et al, 2005) and men only (Cidis Meltzer et al, 2001;Rabiner et al, 2002). Studies involving the serotonin transporter have described localized decreases with age in varying regions (Kalbitzer et al, 2009;Meyer et al, 2001;Reimold et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Ten PET studies published in recent years have used [ 11 C]McNeil 5652 or [ 11 C]DASB to assess the serotonin transporter in depressed subjects and healthy controls. Four of those studies, plus a data re-analysis, noted less binding by the serotonin transporter in brain regions of depressed subjects Oquendo et al 2007;Parsey et al 2006a;Reimold et al 2008;Miller et al 2009b), four studies found more binding by the serotonin transporter in depressed subjects (Reivich et al 2004;Cannon et al 2006b;Cannon et al 2007;Boileau et al 2008), and two studies found no difference between depressed subjects and healthy controls in binding by serotonin transporters in brain regions Bhagwagar et al 2007). Discrepancies are also apparent in the outcome of recent PET studies carried out with [ 11 C]WAY-100635 or [ 18 F]FCWAY to assess serotonin type 1A receptors in depressed subjects and healthy controls.…”
Section: Recent Pet Studies Of Serotonin In Depressive Disordersmentioning
confidence: 99%